Pan‐boreal mapping of forest age and implications for conservation - Yang Liu; Hongyan Zhang; Jianjun Zhao; Shan Yu; Hongbing Chen; Ying Hong; Tongxin Wang; Hui Li; Zhiyong Wang (Conservation Biology, 2026)
Boreal forests, sensitive indicators of global climate change, have age structures and spatial patterns strongly shaped by wildfire and logging that directly affect carbon budgets and biodiversity. In this study, we integrated multisource datasets to develop a quantitative framework for mapping forest age across the boreal biome. We first used change detection methods to identify stand‐replacing disturbances from 1985 to 2020 and then used the time elapsed since disturbance to 2020 as the initial estimate of forest age. We combined forest inventory age records, canopy height, forest landscape integrity, and climatic variables in a random forest model to predict forest age ( R 2 = 0.62, RMSE = 35.46 years). Our findings revealed that boreal forests are generally in a mature state (mean: 112 years; median: 115 years), and their age structure displays a bimodal distribution primarily shaped by fire and logging regimes. Regions with frequent disturbances—such as western Canada and Siberia—are characterized by concentrations of young forests, leading to an increasing proportion of early‐successional stands and a highly heterogeneous landscape mosaic. Some old‐growth patches persist mainly in high‐latitude areas near water bodies, which hold particular ecological value for maintaining long‐term forest stability. We also found that the spatial distribution of forest age is jointly regulated by climatic factors (e.g., low vapor pressure deficit, low solar radiation, and high precipitation) and landscape integrity, which together influence fire regimes and the conditions necessary for long‐term forest persistence. Our results highlighted the need to emphasize landscape‐scale age structure diversity in conservation planning. Environmental characteristics can guide the delineation of priority areas, especially regions with high landscape integrity and low disturbance, to help address current protection gaps. This work improves the understanding of boreal forest age patterns and supports global carbon accounting, systematic conservation planning, and climate change adaptation.